Meningkatkan Kemampuan Kognitif Anak Usia Dini Melalui Metode Karyawisata Di Paud Tk Alkhairaat Bungi Kabupaten Morowali - Wahidah, Lailatul; Najamuddin, Najamuddin; Nurhidayah Ilyas, Sitti (LP. Ma'arif Janggan Magetan, 2024)
Early childhood education is a form of education that aims to optimize children's physical, intellectual and social growth and development. The stimuli given to early childhood must of course be adapted to the stages of development that occur in them. Early childhood has potential that must be developed through stimulation. These potentials are in the form of developmental aspects. To improve the cognitive abilities of early childhood through the field trip method at Paud Tk Alkhairaat Bungi, this research uses qualitative research methods, where an effort or effort by the author can pour ideas or thoughts based on the formation of substantive theories based on empirical data. Data obtained by being present or on location, to conduct research so as to understand all activities and behaviors and things that can help this research. It can be concluded that students can think operationally, by touching, seeing, feeling and intersecting directly with the original source it turns out that it can be easier for students to understand and can develop cognitive abilities in students. If students learn with happy conditions, the material will be more easily digested and well received by students.